PENGARUH BRAND IMAGE PRICE DISCOUNT DAN EXPERIENTIAL MARKETING TERHADAP KEPERCAYAAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA UMKM UTI DHIFA KATERING DI BANYUPUTIH SITUBONDO - Khoirur Roziqin; Yudha Praja; Siti Soeliha (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the influence of Brand Image, Price Discount, and Experiential Marketing on Trust through Customer Satisfaction as an intervening variable in MSME Uti Dhifa Catering in Banyuputih, Situbondo. The sampling technique used in this research is Simple Random Sampling (SRS) with a total of 192 respondents. Data analysis and hypothesis testing in this study employed the Structural – Partial Least Square (PLS-SEM) model. The results show that Brand Image has a positive and significant influence on Customer Satisfaction, Price Discount has a positive but not significant influence on Customer Satisfaction, and Experiential Marketing has a positive and significant influence on Customer Satisfaction. Furthermore, Brand Image has a positive but not significant influence on Trust, Price Discount has a negative and not significant influence on Trust, while Experiential Marketing has a positive and significant influence on Trust. Customer Satisfaction has a positive and significant influence on Trust. Brand Image has a positive and significant influence on Trust through Customer Satisfaction, Price Discount has a positive but not significant influence on Trust through Customer Satisfaction, and Experiential Marketing has a positive and significant influence on Trust through Customer Satisfaction.